Transgenic rats carrying the mouse renin gene: morphological characterization of a low-renin hypertension model - Bachmann, Sebastian; Peters, Jörg; Engler, Eberhard; Ganten, Detlev; Mullins, John (Kidney international, 1992)
Transgenic rats carrying the mouse renin gene—Morphological characterization of a low-renin hypertension model. Transgenic rats [TGR; strain name TGR(mRen2)27] harboring the mouse Ren-2 renin gene have been recently generated as a model for the study of primary hypertension that offers the advantage of a clearly-defined genetic alteration. Expression of the mouse Ren-2 gene causes severe hypertension (200 to 260 mm Hg) which is responsive to converting enzyme inhibitors. Compared to control transgene-negative littermates, plasma renin and angiotensin II values are lowered in TGR, whereas plasma prorenin values are strongly elevated. The adrenal gland in TGR shows marked overexpression of mouse renin messenger RNA; in situ hybridization using a 35S-labelled mouse-renin RNA probe reveals that enhanced renin expression is mainly localized to cells of the zona glomerulosa and outer zona fasciculata. Immunohistochemically, renin protein in the TGR adrenal gland is stored in larger quantities than in controls. Adrenal transgene expression probably accounts for most of the elevated plasma prorenin level in TGR, since bilateral adrenalectomy (ADX) causes a significant decrease in prorenin level (318 ± 79 ng angiotensin I/ml/hr before ADX to 70 ± 43 ng 4 days after ADX, P < 0.0005). In the kidney, renin synthesis is almost completely suppressed in TGR. In situ hybridization demonstrates that few juxtaglomerular afferent arterioles express renin. Immunohistochemically, the TGR kidney shows significantly reduced renin and angiotensin II immuno-reactivity at the afferent arteriole. Ultrastructural analysis of the afferent arteriolar wall frequently shows the complete absence of renin secretory granules since the granular cells are mostly converted into smooth muscle cells. Beginning at an age of approximately four to six months, TGR develop hypertension-related alterations and pathological lesions in various tissues. In the kidney, the wall thickness of arterioles and arteries is strongly increased, and glomerular lesions including different stages of sclerosis are observed. The thoracic aorta displays a considerable increase in tunica media thickness due to both myocyte hypertrophy and interstitial fibrosis. Coronary arteries and arterioles of the heart are thickened and perivascular fibrosis is observed. The data show that TGR(mRen2)27 transgenic rats display all typical characteristics of hypertensive pathology, making them an interesting model for therapeutic interventions. The fact that these changes occur in animals with a single gene difference to normotensive rats makes them a particularly suitable model for studies on gene-related hypertensive processes.
Artikelversion 18. Dezember 2015
Gesehen am 04.12.2023